2015
DOI: 10.1002/2015jd023687
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of sources of errors in seasonal streamflow forecasting over the U.S. Sunbelt

Abstract: Seasonal streamflow forecasts, contingent on climate information, can be utilized to ensure water supply for multiple uses including municipal demands, hydroelectric power generation, and for planning agricultural operations. However, uncertainties in the streamflow forecasts pose significant challenges in their utilization in real‐time operations. In this study, we systematically decompose various sources of errors in developing seasonal streamflow forecasts from two Land Surface Models (LSMs) (Noah3.2 and CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…[] and Mazrooei et al . [], by upscaling the observed precipitation and temperature to the spatial resolution of BCSD (i.e., 1° × 1°) and then applying the downscaling procedure, quantile mapping, adapted by BOR. We did not estimate the downscaling error separately here, since we expect it to be very small as found by Sinha et al .…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[] and Mazrooei et al . [], by upscaling the observed precipitation and temperature to the spatial resolution of BCSD (i.e., 1° × 1°) and then applying the downscaling procedure, quantile mapping, adapted by BOR. We did not estimate the downscaling error separately here, since we expect it to be very small as found by Sinha et al .…”
Section: Results and Analysismentioning
confidence: 99%
“…[] and Mazrooei et al . []. Though we applied the proposed equations – for four test basins, in principle it can be applied to quantify the errors in estimating the observed flows and in estimating the changes in hydrologic attributes for any given watershed.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Such pre-processing may include predictor selections, bias-correction and spatial downscaling, etc. Earlier studies have reported that the pre-processing of climate predictors can potentially include significant uncertainty in the streamflow simulation [26,41,42]. However, the current study has applied a multivariate bias-correction technique, ACCA, to remove model bias in climate predictors while preserving the interdependence between precipitation and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…These suboptimal model parameters result in errors of model outputs. Additionally, LSM simulations are also prone to errors from the uncertainties existing in the forcing data and the lack of scientific understanding in model physics (Mazrooei et al, 2015;Peters-Lidard et al, 2008;Reichle & Koster, 2004).…”
Section: Introductionmentioning
confidence: 99%